2020
DOI: 10.3389/fphar.2020.00681
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Beta Blockers in Takotsubo Syndrome as Compared to Acute Coronary Syndrome

Abstract: Background: Takotsubo syndrome (TTS) and acute coronary syndrome (ACS) patients have a similar mortality rate. In this study, we sought to determine the short-and long-term outcome of TTS patients as compared to ACS patients both treated with beta-blockers. Objectives: In the present study we described the data of 5 years of follow up of 103 TTS and 422 ACS patients both treated with beta-blockers. Methods: Data from TTS patients were included retrospectively and prospectively, ACS patients were included retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A multicenter study, involving 36 patients, showed that 30-day treatment with an oral betablocker initiated at the time of diagnosis, provided no advantage in improvements of left ventricular ejection fraction [ 23 ]. Kummer et al reported, that betablocker therapy did not ameliorate long-term survival in TTS patients [ 24 ]. Similarly, in an analysis of a TTS registry, Templin et al showed comparable death rates at 1 year whether patients with TTS are treated with betablockers or not [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study, involving 36 patients, showed that 30-day treatment with an oral betablocker initiated at the time of diagnosis, provided no advantage in improvements of left ventricular ejection fraction [ 23 ]. Kummer et al reported, that betablocker therapy did not ameliorate long-term survival in TTS patients [ 24 ]. Similarly, in an analysis of a TTS registry, Templin et al showed comparable death rates at 1 year whether patients with TTS are treated with betablockers or not [ 25 ].…”
Section: Discussionmentioning
confidence: 99%